The Low-Density University - Maloney, Edward J. (Johns Hopkins University Press, 2020)
COVID-19 triggered an existential crisis for American higher education. Faced with few safe choices, most colleges and universities switched to remote learning during the 2020 spring semester. The future, however, provides more choices about how institutions can fulfill their mission of teaching and research. But how do we begin to make decisions in an uncertain and shifting environment? In this concise guide, authors Edward J. Maloney and Joshua Kim lay out clear ways colleges and universities can move forward in safe and effective ways. The Low-Density University presents fifteen scenarios for how colleges and universities can address the current crisis from a fully online semester to others with students in residence and in the classroom. How can changing the calendar or shifting to hybrid models of blended classrooms impact teaching, learning, and the college experience? Could we emerge from this crisis with new models that are better and more adapted to today's world? The Low-Density University focuses primarily on teaching and learning, but student life (housing, athletics, health, etc.) are core to the college experience. Can we devise safe and effective ways to preserve the best of that experience? The lessons here extend beyond the classroom. Just as the pandemic will change American higher education, the choices we make now will change what college looks like for generations to come.